Does Music affect Technostress? - Hughes, Stephanie G. (My University, 2016)
This research investigates technostress and how its effects may be mitigated through the use of music. In general, technostress is a form of stress induced specifically by technology use. We hypothesize in this study that musical preference and the application of background music will impact subjects experiencing technostress. Our ultimate goal is to determine ways technostress can be reduced. Our research method utilized an experiment where 22 students completed a stressful online task while listening to music clips. Each clip contained silence as well as upbeat and relaxing music arranged in random order. The online task was manipulated to induce stress by: showing a ticking hour glass; providing a large red count down timer; telling the students they must get an 80% or higher on a set of questions; and, having too much work to complete under the time constraint. Stress levels were measured using a multi-method approach featuring a galvanic skin sensor, a post-experiment questionnaire, and measures of task accuracy and timeliness. The data was analyzed to determine if the presence of music affected technostress. The results indicated music order was significantly related to stress levels and task accuracy, and appeared to be more important than the music selections. Moreover, user music preference was a strong predictor of both galvanic skin response and accuracy of task completion. Overall, starting the experiment with silence or relaxing music tended to reduce stress levels throughout the experience but did not necessarily increase the accuracy of the task. We provide suggestions for future research to look closer at these factors.